Antifungal activity of Bacillus amyloliquefaciens against Fusarium oxysporum f. sp. cubense race 1 - Cruz-Martín, Mileidy (2021)
Introduction. Due to the absence of totally effective either economically viable chemical agents for the control of Fusarium wilt, the use of antagonistic microorganisms is of great interest since it could represent a more economically and ecologically sustainable alternative. Objective. To analyze the antifungal effect of the Bacillus amyloliquefaciens CCIBP-A5 strain against Fusarium oxysporum. Materials and methods. The work was carried out in the Laboratory of Applied Microbiology of the Instituto de Biotecnología de las Plantas, Cuba, between September 2017 and June, 2018. The in vitro and in vivo antifungal activity of its culture filtrate and cell against F. oxysporum has been assayed. Results. The results indicated that the metabolites present in the culture filtrate of B. amyloliquefaciens CCIBP-A5 significantly influenced the growth and morphology of the mycelium and the conidia. They also caused oxidative damage to the lipid molecules of F. oxysporum. In addition, this strain showed inhibitory effects on the development of the disease under controlled conditions. These aspects are key when selecting a bacterial candidate as a biological control agent. Conclusions. The results showed that the B. amyloliquefaciens CCIBP-A5 strain, isolated from Musa sp., had an in vitro antifungal effect against the vegetative and reproductive structures of Foc race 1 as well as on the Musa spp.-F. oxysporum interaction. This strain is suggested for the development of a bioproduct for Fusarium wilt management.